Self-Awareness: Analysis of Nursing Management in Treating Patients with Type 2 Diabetes Mellitus - Leni Rozani; Ferasinta Ferasinta (KHD Production, 2024)
Diabetes Mellitus type 2 is a disease with the largest number of sufferers of all existing diabetes diseases. Diabetes mellitus type 2 can be prevented by modifying lifestyle and lifestyle. This study aims to determine the self-awareness of groups at high risk of developing Diabetes Mellitus. This research uses a qualitative descriptive research method with a case study approach. Data was obtained by interviewing three high-risk participants who had a family history of Diabetes Mellitus. The interview results were analyzed using the Corbin and Strauss method which consists of three stages, namely open coding, axial coding and selective coding. The results of the research show that there is a similar pattern and produce selective coding, namely the lack of knowledge, attitudes and behavior in preventing Diabetes Mellitus which is not yet good in the community. Suggestions in the research are for health service providers to be more active in terms of prevention, such as providing education to residents so that residents can maintain their health. independently, especially in terms of a healthy lifestyle.